Perspective: Reducing SARS-CoV2 Infectivity and Its Associated Immunopathology - Dubey, Abhishek; Dahiya, Surbhi; Rouse, Barry T.; Sehrawat, Sharvan (Frontiers in Immunology, 2020)
COVID-19 has become difficult to contain in our interconnected world. In this article, we discuss some approaches that could reduce the consequences of COVID-19. We elaborate upon the utility of camelid single domain antibodies (sdAbs), also referred to as nanobodies, which are naturally poised to neutralise viruses without enhancing the infection. Smaller sized sdAbs that can easily be selected using microbes or the subcellular organelle display methods can neutralize SARS-CoV2 infectivity. We also discuss issues related to their production using scalable platforms. The favourable outcome of the infection is evident in patients when the inflammatory response is adequately curtailed. Therefore, we also discuss approaches used to mitigate hyperinflammatory reactions initiated by SARS-CoV2 but orchestrated by immune mediators.